Electrohydrodynamic 3D Nanoprinting: Parallel, Multi‐Material Electrohydrodynamic 3D Nanoprinting (Small 13/2020). Issue 13 (3rd April 2020) - Chen, Mojun; Lee, Heekwon; Yang, Jihyuk; Xu, Zhaoyi; Huang, Nan; Chan, Barbara Pui; Kim, Ji Tae
Abstract : Improving productivity and material diversity is a key challenge for 3D printing to become a true manufacturing platform. In article number 1906402, Ji Tae Kim and co‐workers develop a parallel electrohydrodynamic 3D nanoprinting method for functional materials. The method exploits an unusual electric field distribution created by cross talk of neighboring printing nozzles to steer the ejection paths of the ink, enabling on‐demand control over shape, placement, and material mixing. The new manufacturing route developed here provides insights into the heterogeneous fabrication and 3D integration of functional nanomaterials.